PENGEMBANGAN SARANA KEGIATAN DAN SUMBER BELAJAR DI TAMAN KANAK-KANAK - NURHASANAH, NURHASANAH (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2018)
One of the mandates of the founders of the Indonesian nation as outlined in the 1945 constitution was to educate the life of the nation. One of the efforts taken to fulfill this very goal is through the world of education. Education is the main key to encourage the improvement of the quality of human resources so that they can compete with other nations. Through early childhood education institutions, the government and the community have taken a very big role in the development of education in Indonesia. Early childhood education institutions can easily emerge, grow, and develop, considering the formation process is quite easy. There are so many early childhood education institutions that have sprung up even like mushrooming, not only in big cities but in remote rural areas. Indeed, this has become a distinctive achievement for this nation, given that community participation is very high in playing a role in the world of education through the establishment of various early childhood education institutions. Apart from all these positive aspects, several problems emerged regarding these early childhood education institutions. The biggest problem is the management of facilities, this is due to the lack of knowledge of the managers of early childhood education institutions on the development and management of infrastructure and the use of learning resources.